Use of sisal fiber and cement to improve load bearing capacity of mud blocks. (December 2022) - Alene, Temesgen Ejigu; Mohammed, Tesfaye Alemu; Gualu, Alemayehu Golla
Abstract: Using soil as a construction material for masonry works have been indigenous technology. The present research investigates on use of sisal fibres and cement additives to enhance compressive strength of properties of mud block to advance traditional native knowledge and meet current construction material standard qualities. An experiment with total of twenty-four mixes consisting of 96 blocks was designed with mixes of 0–15 % cement; 0–1.25 % sisal fiber proportional to clay soil dry mass. At 28 days, compressive strength and density tests were performed as per ASTM standards. Test results showed use of sisal fibers and cement increased compressive strength of mud blocks up to 210.1 %. Optimum mix design for enhanced mud block compressive strength performance were 10 % cement and 1 % sisal fiber composition. Graphical Abstract: ga1